Analisis Problematika Guru dalam Mengintegrasikan Islam pada Pembelajaran Biologi di Madrasah Aliyah Negeri Kabupaten Sijunjung dan Kota Sawahlunto - Imelda Yanti; Ardi Ardi (Lembaga Yasin AlSys, 2026)
Although the integration of Islam and science, particularly in biology instruction, has been widely discussed, studies that specifically examine the challenges teachers face in implementing such integration at Madrasah Aliyah Negeri in Sijunjung Regency and Sawahlunto City remain limited. This study aimed to analyze the problems encountered by biology teachers in integrating Islamic values into science learning at Madrasah Aliyah Negeri in Sijunjung Regency and Sawahlunto City. A descriptive quantitative approach with a survey design was employed, involving six biology teachers selected through purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire supported by interviews and documentation, and were analyzed descriptively through the calculation of percentages, mean scores, and data categorization. The findings indicate that the main problems faced by teachers include limited availability of biology teaching materials integrated with Islamic values, differences in teachers’ educational backgrounds, limited mastery of Islamic subject matter, and the absence of standardized models or guidelines for biology–Islam integrated instruction. These conditions have led to suboptimal implementation of biology–Islam integration in science learning, which still largely depends on each teacher’s individual initiative. The study concludes that the success of integrating biology and Islam is strongly influenced by teachers’ competency readiness, the availability of integrated teaching materials, and policy support from the madrasah. The implications of this research include theoretical contributions to enriching the discourse on the integration of religious sciences and natural sciences, as well as practical implications for madrasahs and policymakers in designing teacher training, developing teaching materials, and formulating systematic and applicable integrative learning models.